The safety of talimogene laherparepvec for the treatment of advanced melanoma. Issue 2 (1st February 2017) - Gangi, Alexandra; Zager, Jonathan S.
ABSTRACT: Introduction : Talimogene laherparepvec (T-VEC, IMLYGIC) is an oncolytic herpes virus type I used as intralesional therapy for the treatment of unresectable metastatic melanoma in a cutaneous, subcutaneous, or nodal location. Talimogene laherparepvec selectively replicates within and lyses tumor cells while producing granulocyte macrophage colony-stimulating factor (GM-CSF), which may promote an immune mediated antitumor response. Areas covered : The US Food and Drug Administration approved Talimogene laherparepvec in late 2015 following the completion of phase I, II and III trials that demonstrated safety and efficacy. Current NCCN practice guidelines have added Talimogene laherparepvec as a primary treatment for stage IIIB/C and stage IVM1a melanoma patients with evidence of good durable response rates, and this article sets out to review the use and safety and efficacy of T-VEC Expert opinion : Treatment options for locally advanced and metastatic melanoma are expanding with new developments in immunotherapy and immune checkpoint inhibitors. The ideal treatment of metastatic melanoma continues to be multimodal, combining systemic treatments, intralesional and regional therapies, surgery and radiotherapy to achieve optimal outcomes. Use of talimogene laherparepvec as intrelsional therapy has demonstrated promising effects in select patients with advanced melanoma. Future directions for Talimogene laherparepvec include combination therapies with other systemic immunotherapies such as anti-CTLA-4 antibody and anti-PD-1 drugs.